The temporal variation of organic carbon during the pre-monsoon and post-monsoon seasons in Pahang river estuary, Pahang, Malaysia - Yunus, Kamaruzzaman; Abdurahman, Siti Waznah; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Ong, Meng Chuan (Oriental Scientific Publishing Co., 2010)
The percentage of organic carbon contents of 62 bottom sediments in Pahang river- estuary were analyzed using the wet dichromate oxidation method. The sediments particle sizes at the same stations were also measured using the dry sieving and laser diffraction methods. In this study, the concentrations of organic carbon are relatively higher during pre-monsoon season and become much lower during the post-monsoon season. The average concentrations of organic carbon for both premonsoon and post-monsoon seasons are 1.61% and 0.88% respectively. This finding indicates that the annual seasonal changes that occur in Pahang river- estuary might probably have the important role in regulating the concentrations of organic carbon.